Geotechnical applications for earthquake engineering research advancements - Sitharam, T. G., 1961- (Information Science Reference, 2012)
"This book has collected chapters from experts from around the world in a variety of applications, frameworks, and methodologies in earthquake engineering, and presents this valuable research in a form that serves as a handy reference and research guide to practitioners and academics alike"--Provided by publisher.
Keywords: Soil mechanics.; Engineering geology.; Earthquake engineering.; elektronické knihy; electronic books